Association between lifestyle risk factors and mortality in the Mexico City prospective study - Ferrero-Hernández, Paloma; O’Donovan, Gary; Petermann-Rocha, Fanny; Christofaro, Diego G. D. [UNESP]; Cristi-Montero, Carlos; Marques, Adilson; Nascimento, Marcelo de Maio; Farías-Valenzuela, Claudio; Rezende, Leandro F. M.; Ferrari, Gerson (Springer Nature, 2025)
Unhealthy lifestyles risk factors, such as smoking, alcohol consumption, physical inactivity, poor diet, and obesity, have been associated with a higher risk of all-cause and cause-specific mortality. However, composite score of these unhealthy behaviours has not been considered, particularly in Latin American populations. Herein, we examined the association of lifestyle risk factors score with all-cause and cause-specific mortality in Mexican adults. A total of 159,517 adults from the Mexico City Prospective Study (MCPS) were included. Data on sociodemographic, lifestyle risk factors and medical histories was collected through a self-reported baseline questionnaire in a census-style door-to-door interviews. Lifestyle risk factors assessment was based on five modifiable lifestyle risk factors and their respective cut-off points according to current health recommendations, including obesity, physical inactivity, tobacco, alcohol consumption and fruits and vegetables intake. Multivariable Cox regression models were used to estimate the associations of lifestyle risk factor score (ranging from 0 to 5) with all-cause and cause-specific mortality (cardiovascular disease, renal or hepatobiliary diseases, diabetes, respiratory diseases, cancer and all-cause mortality). We excluded the first 2, 5, 10, and 15 years of follow-up to account for reverse causation bias. We found a high prevalence (77%) of Mexican adults, with two or more lifestyle risk factors. Hazard ratio for respiratory diseases and renal or hepatobiliary diseases were 1.86 (95%CI: 1.45–2.39) and 2.00 (95%CI: 1.60–2.52) comparing participants with 4–5 lifestyle risk factors vs. those with none. For all-cause mortality, participants with 4–5 lifestyle risk factors had a 49% (HR: 1.49; 95%CI: 1.03–2.16) higher risk as compared to participants with none. The magnitude of the associations increased as the exclusion of follow-up time increased after 2, 5, 10 and 15 years. There was a positive association between the number of lifestyle risk factors and all-cause and cause-specific mortality, showing the highest rate of respiratory, renal or hepatobiliary and all-cause mortality among participants with 4–5 lifestyle risk factors. After accounting for reverse causation, associations were stronger.
Keywords: Lifestyle; Mortality; Non-communicable diseases; Reverse causation; Risk factor